Predictors of major adverse cardiovascular events in patients with treated with covered stents - Savur, Ümeyir; Akhundova, Aysel; Çatalbaş, Başak; Karaca, İbrahim Oğuz (My University, 2024)
Background: Coronary artery perforation (CAP) is a rare, life-threatening complication of percutaneous coronary intervention (PCI). PTFE-coated stents are highly successful and lifesaving in the treatment of coronary perforation. The incidence of thrombosis and restenosis in the PTFE-covered stent is higher than in standard stents. The aim of this study was to evaluate the clinical outcomes of PTFE-covered stents for CAP. Materials and methods: We evaluated a total of 38 patients who were treated with PTFE-coated stents for coronary perforation from January 2012 to January 2022 at a single high-volume center, Medipol University Hospital in Turkey. The primary endpoint was the composite of major adverse cardiovascular events (MACEs). Results: The one-year outcomes of the patients who had PTFE-coated stents implanted after CAP were investigated. A total of 38 patients, 22 (58%) males and 16 (42%) females, were included. The mean age was 69.7±11.4 years. MACE developed in 37% of the population (14 patients) in the follow-up. The target vessel revascularization (TVR) rate at one year was 36.8% (14 patients), the target lesion revascularization (TLR) rate at one year was 21% (8 patients), the incidence of death was 10.5% (4 patients), of myocardial infarction 21.1% (8 patients). Conclusions: Today, although the majority of coronary perforation cases are successfully treated with PTFE--coated stents, the one-year outcome of MACE in CS implanted patients is high. These results showed that such patients should be closely monitored.

Kontext: Perforace koronární tepny (coronary artery perforation, CAP) je vzácnou, ?ivot ohro?ující komplikací perkutánní koronární intervence (PCI). Vysoce úsp?šnou a ?ivot zachra?ující metodou lé?by CAP je implantace stent? pota?en?ch polytetrafl uorethylenem (PTFE). Incidence trombózy a restenózy p?i pou?ití stent? pota?en?ch PTFE je vyšší ne? p?i implantaci standardních stent?. Cílem této studie bylo zhodnotit klinické v?sledky pou?ití stent? pota?en?ch PTFE p?i ?ešení CAP. Materiály a metody: Analyzovali jsme údaje celkem 38 pacient? s implantací stent? pota?en?ch PTFE po CAP provedenou v období mezi lednem 2012 a lednem 2022 na jednom pracovišti s vysok?m objemem t?chto v?kon? (Medipol University Hospital v tureckém Istanbulu). Primárním sledovan?m parametrem byl souhrn záva?n?ch ne?ádoucích kardiovaskulárních p?íhod (major adverse cardiovascular event, MACE). V?sledky: Hodnotili jsme jednoro?ní v?sledky pacient? s implantací stent? pota?en?ch PTFE po CAP. Do studie bylo za?azeno celkem 38 pacient?; 22 (58 %) mu?? a 16 (42 %) ?en pr?m?rného v?ku 69,7 ± 11,4 roku. B?hem sledování došlo ke vzniku MACE u 37 % daného souboru (14 pacient?). Do jednoho roku byla revaskularizace cílové tepny (target vessel revascularization, TVR) provedena u 36,8 % (14 pacient?) a revaskularizace cílové léze (target lesion revascularization, TLR) u 21 % (8 pacient?), incidence úmrtí dosáhla 10,5 % (4 pacienti) a infarktu myokardu 21,1 % (8 pacient?). Záv?ry: I kdy? se dnes v?tšina p?ípad? perforace koronární tepny úsp?šn? ?eší zavedením stent? pota?en?ch PTFE, je jednoro?ní incidence MACE u pacient? s implantací takov?ch stent? vysoká. Naše v?sledky tak prokázaly, ?e uvedené pacienty je nutno d?sledn? sledovat.
Keywords: Coronary Artery Perforation; Covered Stent; Percutaneous Coronary Intervention; Polytetrafl Uoroethylene (PTFE)-Coated Stents; Kryt? Stent; Perforace Koronární Tepny; Perkutánní Koronární Intervence; Stenty Pota?ené Polytetrafl Uorethylenem (PTFE)